ANALYSIS OF COMMUNICATION PATTERNS IN THE NEK NGEMANIS TRADITION THROUGH THE LASWELL COMMUNICATION MODEL - Gustin, Gustin; Arifah, Arifah; Putri, Sekar; Fadillah, Siti Nurul; Azpa, Pani; Alnady Alphiry, Mohammed Eprahim (MEDIOVA: Journal of Islamic Media Studies, 2023)
Marriage traditions in Indonesia are rules regarding marriage based on the customs that exist in Indonesia. This wedding procession has its own customs in each region. This tradition is usually carried out by predecessors or ancestors in the area, so that marriage traditions in Indonesia have different forms. Unfortunately, now traditional marriage traditions have begun to fade with the times. The fading of existing culture is due to increasingly popular technological sophistication, so that people are more interested in the existence of the virtual world rather than preserving existing traditional culture. However, there is still a marriage tradition that persists in Indonesia, namely the marriage tradition of nek ngemanis in Pisang Hamlet, Kelapa Regency. This research aims to analyses the nek ngemanis marriage tradition in maintaining its existence through the Lasswell model of communication patterns. This qualitative research uses case study methodology with in-depth interviews and documentation as data collection methods. The results of the research prove that the nek ngemanis marriage tradition still survives today because there is an effective communication process in society by applying the Laswell communication pattern, namely who says what in which channel to whom with what effect. Based on these communication patterns, it was found that there are five important elements in communication, namely the communicator, message, communicant, media, and reciprocal effects. So, the results of this research show that the message conveyed and the inherent meaning of the nek ngemanis marriage tradition still exists amidst the current popularity of sophisticated technology.